Overexpression of EI2BL promoted human non-small cell lung cancer progression by inducing cell EMT phenotype. Issue 3 (5th October 2019) - Li, Hao-Ran; Qiu, Bai-Quan; Gao, Jian; Jin, Chun; Jiang, Jia-Hao; Ding, Jian-Yong
Abstract : Aims: To unveil the role of EI2BL in non-small cell lung cancer (NSCLC) and the relationship between expression of EI2BL and the prognosis of patients with NSCLC. Methods: Immunohistochemistry (IHC), western blot analysis, immunofluorescence and real-time quantitative PCR (RT-qPCR) were used to evaluate EI2BL protein and mRNA levels in NSCLC and corresponding peritumour tissues. Cell Counting Kit-8, transwell assay and wound healing assay were used to analyse the abilities of cell proliferation, invasion and migration. In addition, the analysis of epithelial-mesenchymal transition (EMT) markers was also assessed by western blot analysis, RT-qPCR and immunofluorescence. Tissue micro-array analysis of 200 NSCLC cases was used to assess the relationship between EI2BL expression and clinicopathological characteristics. Moreover, the prognostic role of EI2BL in 200 patients with NSCLC was evaluated by Cox regression models and Kaplan-Meier methods. Results: Elevated EI2BL expression was more common in NSCLC tissues than paired peritumour tissues in both mRNA and protein level. EI2BL promoted the proliferation, invasion and migration of NSCLC cells. In addition, aberrant EI2BL expression might modulate the expression of key molecules of EMT by ERK1/2 signal pathway. The expression of EI2BL was significantly associated with tumour stage, lymph node metastasis and tumour size. Moreover, higher expression of EI2BL in patients with NSCLC had a poor overall survival rate. Conclusions: Our study illustrated that elevated expression of EI2BL promoted NSCLC cell proliferation, migration and invasion and EI2BL overexpression may be a reliable biomarker of poor prognosis.